Dallas MegaShelter Medical Operations Response to Hurricane Harvey. (6th December 2017) - Liu, E. Liang; Morshedi, Brandon; Miller, Brian L.; Miller, Ronna; Isaacs, S. Marshal; Fowler, Raymond L.; Chung, Wendy; Blum, Ruby; Ward, Breanne; Carlo, John; Hennes, Halim; Webster, Frank; et al.
Abstract: On August 25, 2017, Hurricane Harvey made landfall near Corpus Christi, Texas. The ensuing unprecedented flooding throughout the Texas coastal region affected millions of individuals. 1 The statewide response in Texas included the sheltering of thousands of individuals at considerable distances from their homes. The Dallas area established large-scale general population sheltering as the number of evacuees to the area began to amass. Historically, the Dallas area is one familiar with "mega-sheltering, " beginning with the response to Hurricane Katrina in 2005. 2 Through continued efforts and development, the Dallas area had been readying a plan for the largest general population shelter in Texas. ( Disaster Med Public Health Preparedness . 2019;13:33–37)